Islamic and Customary Inheritance Law: Addressing Differences and Similarities in the Distribution of Property - Datumula, Sarpika (Journal of Nafaqah, 2025)
This article examines the inheritance systems in Indonesia by comparing the normative structure of Islamic inheritance law with the flexible, community-based principles of customary (adat) inheritance practices. Using a qualitative, literature-based approach, the study analyzes the core principles, gender dynamics, and distribution mechanisms within both systems. Islamic inheritance law, as codified in the Qur’an and classical jurisprudence, follows fixed shares assigned to specific heirs, reflecting a theologically grounded notion of proportional justice. In contrast, customary inheritance systems such as the patrilineal Batak, matrilineal Minangkabau, and bilateral Javanese models are based on kinship norms, emotional ties, and deliberation, allowing for more context-sensitive arrangements. The discussion highlights key points of divergence and convergence between the two systems, particularly in terms of legal authority, gender roles, and adaptability. It also explores how Indonesian families navigate these plural frameworks, often blending formal rules with informal negotiations to achieve perceived fairness. The study concludes that legal pluralism, rather than posing a conflict, offers an opportunity for harmonization through contextual interpretation, inclusive dialogue, and the integration of religious and cultural values.